2021
DOI: 10.1186/s12890-021-01594-4
|View full text |Cite
|
Sign up to set email alerts
|

Residual respiratory impairment after COVID-19 pneumonia

Abstract: Introduction The novel coronavirus SARS-Cov-2 can infect the respiratory tract causing a spectrum of disease varying from mild to fatal pneumonia, and known as COVID-19. Ongoing clinical research is assessing the potential for long-term respiratory sequelae in these patients. We assessed the respiratory function in a cohort of patients after recovering from SARS-Cov-2 infection, stratified according to PaO2/FiO2 (p/F) values. Method Approximately o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 17 publications
(20 reference statements)
0
11
2
Order By: Relevance
“…While there is evidence that post-COVID-19 patients with mild to moderate disease have preserved lung volumes, 26 we found a significantly lower TLC in subjects after mild to moderate infection compared with controls. This is in line with previous findings of a reduction in TLC beginning after mild COVID-19.…”
Section: Discussioncontrasting
confidence: 94%
“…While there is evidence that post-COVID-19 patients with mild to moderate disease have preserved lung volumes, 26 we found a significantly lower TLC in subjects after mild to moderate infection compared with controls. This is in line with previous findings of a reduction in TLC beginning after mild COVID-19.…”
Section: Discussioncontrasting
confidence: 94%
“… 6 , 7 Previous studies of COVID-19 survivors have shown a continuously recovery in lung function though variable degrees of residual abnormalities still remain. 8 , 9 , 10 , 11 , 12 The longest duration of follow-up was around 1 year and only a small number of subjects were studied. 13 Moreover, no longitudinal cohort studies have provided detailed data regarding the lung-function trajectories in survivors after discharge.…”
Section: Introductionmentioning
confidence: 99%
“…After the first wave of the global coronavirus disease 2019 (COVID-19) pandemic, it became increasingly clear that the pulmonary sequelae often persist far beyond the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Apart from the diverse cluster of symptoms collectively coined “long COVID” [ 1 ] (breathlessness, chest pain, and fatigue), several studies have documented various degrees of reduced pulmonary diffusing capacity of carbon monoxide (DLco) in previously hospitalised patients up to 12-months post-discharge [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. In many cases, concomitant residual radiological abnormalities are present on high-resolution chest CT, (HRCT) most typically ground-glass opacities (GGO), interlobular septal thickening, and reticulations [ 4 , 8 ].…”
Section: Introductionmentioning
confidence: 99%